Antibacterial Activity of Milkwood Bark Ethanol Extract (Alstonia Scholaris (L.) R. Br.) against Staphylococcus Aureus and Escherichia Coli - Sitti Khairul Bariyyah; Muhammad Munawar Khalil; Rani Dewi Pratiwi; Elsye Gunawan (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Milkwood bark (Alstonia scholaris (L.) R. Br.) is one of the medicinal plants of the genus Alstonia. This plant is traditionally used by the community as a medicine for diarrhea, diabetes, malaria, hemorrhoids, and antihypertensives. This plant contains secondary metabolites that have the potential as antibacterial such as alkaloids, flavonoids, saponins and tannins. The purpose of this study was to determine the inhibition of antibacterial activity and the most effective concentration in inhibiting Staphylococcus aureus and Escherichia coli. The sample used in this study was milkwood bark, the sample was extracted by maceration method using 96% ethanol as solvent. The antibacterial testing method used in this study was disc diffusion. The study used a completely randomized design with 9 treatments, namely 1000 ppm, 750 ppm, 500 ppm, 250 ppm, 100 ppm, 50 ppm, 10 ppm, Ciprofloxacin (positive control), sterile distilled water (negative control). The results of the antibacterial activity test at a concentration of 500 ppm showed that milkwood bark extract could inhibit the growth of S. aureus by 8.22 mm and at a concentration of 250 ppm showed that milkwood bark extract could inhibit the growth of E. coli by 8.75 mm. From the test results, it can be concluded that milkwood bark (A. scholaris (L.) R. Br.) has antibacterial activity that has moderate potential in inhibiting S. aureus and E. coli.